2019
DOI: 10.1016/j.drugalcdep.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic cathinone MDPV enhances reward function through purinergic P2X7 receptor-dependent pathway and increases P2X7 gene expression in nucleus accumbens

Abstract: Background and Purpose: Purinergic P2X7 receptors are present on neurons, astrocytes and microglia and activated by extracellular ATP. Since P2X7 receptor activation releases endogenous substrates (e.g., pro-inflammatory cytokines, dopamine, and glutamate) that facilitate psychostimulant reward and reinforcement, we investigated the hypothesis that the synthetic cathinone 3,4-methylenedioxypyrovalerone (MDPV) produces rewarding effects that are dependent on active P2X7 receptors. Methods: Reward function was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Previous studies also showed an important presence of P2X7R mRNA in this area within the adult rat brain (Yu et al 2008). This area has been traditionally associated to reward and reinforcement functions (Olds and Milner 1954), which goes in line with recent studies showing the involvement of the P2X7R on reward enhancement produced by psycho-stimulant drugs (Gentile et al 2019). Likewise, a remarkable high level of P2rx7-EGFP expression was detected in the SFO, a circumventricular organ of the brain associated to osmoregulation and fluid balance (McKinley et al 2019).…”
Section: The Septum and Circumventricular Organssupporting
confidence: 78%
“…Previous studies also showed an important presence of P2X7R mRNA in this area within the adult rat brain (Yu et al 2008). This area has been traditionally associated to reward and reinforcement functions (Olds and Milner 1954), which goes in line with recent studies showing the involvement of the P2X7R on reward enhancement produced by psycho-stimulant drugs (Gentile et al 2019). Likewise, a remarkable high level of P2rx7-EGFP expression was detected in the SFO, a circumventricular organ of the brain associated to osmoregulation and fluid balance (McKinley et al 2019).…”
Section: The Septum and Circumventricular Organssupporting
confidence: 78%
“…BBG prevented all these LID-associated dopaminergic alterations, which might eventually result from direct effects of P2X7R located in dopamine cells (Heine et al, 2007 ) and striatal dopamine terminals (Carmo et al, 2014 ). However, although the presence of P2X7R mRNA and protein in the striatum and substantia nigra is established (Amadio et al, 2007 ; Kaczmarek-Hajek et al, 2018 ; Crabbé et al, 2019 ; Gentile et al, 2019 ) and there is evidence for an increased P2X7R density in the striatum upon decreasing dopaminergic innervation (Ferrazoli et al, 2017 ; Crabbé et al, 2019 ), the cellular localization of P2X7R is essentially unknown, and there is no data currently available to ascribe the presence of P2X7R to different neuronal populations (e.g., D1R or D2R) in nigrostriatal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, several hub genes associated with small nucleolar RNA (including several LOC genes) and ribonucleoproteins ( Hnrnpu ) that are key in RNA processing (e.g., methylation, uridylation, and stabilization) stand out when Ctx and HC groups are compared, highlighting withdrawal features as opposed to extinction 49,54 . Gene co-expression between Ctx and Ext reveals cell signaling ( Camkv ) and metabolism processes ( Atp5f ), perhaps critical to instrumental or contextual WD/Ext learning 51,52,55 . Notable overlapping results between HC and Ext groups identified several likely regulatory (hub) genes involved in ion transporters and channels ( Slc12a8/9, Scn11a ), estrogen actions ( Esrrb ), and myelin maintenance ( Mag ), potentially signaling spontaneous extinction- or withdrawal-associated processes of cocaine 4244,50,53,99102 .…”
Section: Discussionmentioning
confidence: 99%